Highly enantioselective “inherently chiral” electroactive materials based on a 2,2′-biindole atropisomeric scaffold - Arnaboldi, Serena (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Chiral oligothiophene monomers with C(2) symmetry, based on 3,3′-bithiophene atropisomeric cores with high racemization barriers, have recently been shown to provide excellent chiral starting materials with high electroactivity for the easy preparation of enantiopure electroactive films endowed with powerful chirality manifestations. We now introduce an inherently chiral monomer based on a 2,2′-biindole core, as the prototype of a new inherently chiral monomer family, whose properties could be modulable through functionalization of the pyrrolic N atoms. By fast, regular electrooligomerization the new monomer yields inherently chiral films with high, reversible electroactivity and, above all, impressive enantioselectivity towards very different chiral probes, some of pharmaceutical interest, as general-scope electrode surfaces. Such results, while opening the way to a new, attractive inherently chiral selector class, nicely confirm the general validity of the inherent chirality strategy for chiral electrochemistry. Furthermore, the enantioselectivity of the new selectors not only holds with electroactive chiral probes, but also with circularly polarized light components as well as electron spins, resulting in good chiroptical and spin filter performances, which suggests fascinating correlations between the three contexts.